Combination IETA Ultrasonographic Characteristics Simple Scoring Method With Tumor Biomarkers Effectively Improves the Differentiation Ability of Benign and Malignant Lesions in Endometrium and Uterine Cavity - Lin, Dongmei; Zhao, Liang; Zhu, Yunxiao; Huang, Yujun; Yuan, Kun; Liu, Wenfen; Li, Shengli; Guo, Xia; Hao, Yi (Frontiers in Oncology, 2021)
Objectives To evaluate International Endometrial Tumor Analysis (IETA) ultrasonographic characteristics simple scoring method and tumor biomarkers for the diagnosis of uterine cavity and endometrial lesions. Methods We classified and scored the normalized description of IETA ultrasonic characteristics, according to IETA expert consensus literature, previous IETA-related research articles, and the previous research experience of this project group. We conducted a retrospective analysis of the ultrasound images of 594 patients enrolled from January 2017 to June 2020, scored them item by item, and finally calculated the total score of each case. Meanwhile, we combined the results of seven tumor biomarkers. The objective was to evaluate the sensitivity, specificity, coincidence rate, and the area under receiver operating characteristic (ROC) curve of IETA ultrasonographic characteristics simple scoring method and tumor biomarkers for benign and malignant uterine cavity or endometrial lesions. The diagnostic efficiency between the combined method and the single method was compared. Results A total of 594 cases were confirmed by postoperative pathology or surgery records, including 475 benign lesions and 119 malignant lesions. In the simple ultrasound scoring method, the average score of benign lesions was 3.879 ± 1.279 and that of malignant lesions was 9.676 ± 4.491. If ≥6.5 points was taken as the cutoff value for the judgment of malignant lesions, the sensitivity, specificity, coincidence rate, and the area under receiver operating characteristic (ROC) curve (AUC) were 76.5%, 96.0%, 92.1%, and 0.935, respectively. The difference in tumor antigen 19-9 (CA19-9) and human epididymal protein 4 (HE4) between benign and malignant lesions was statistically significant (all p ≤ 0.01). The other five tumor biomarkers (CA125, CA15-3, SCC-Ag, AFP, and CEA) showed no statistically significant difference in benign and malignant lesions. If the value of CA19-9 ≥13.96 U/ml was taken as cutoff value, the sensitivity, specificity, and coincidence rate of the diagnosis of endometrial benign and malignant lesions were 54.8%, 74.7%, and 70.7%, respectively, and the AUC was 0.620. If the value of HE4 ≥ 39.075 pmol/L was taken as cutoff point, the sensitivity, specificity, coincidence rate, and AUC were 77.4%, 67.9%, 69.8%, and 0.796, respectively. The sensitivity was increased to 97.6% and the AUC was 0.939 when IETA ultrasound characteristics simple scoring method combined CA19-9 and HE4 in parallel test. Conclusions In IETA ultrasound characteristics simple scoring method, with ≥6.5 points as the cutoff value, it could quickly and accurately assess the benign and malignant in uterine cavity and endometrial lesions, with high diagnostic value. The diagnostic efficacy of seven tumor biomarkers was all mediocre. Combining with these two methods, the comprehensive diagnosis could improve sensitivity and accuracy and reduce the risk of missed diagnosis.